Path Coefficient Analysis in Pearl Millet - Manga, V K; Gupta, B S; Saxena, M B.L (Annals of Arid Zone, 2016)
Path coefficient and variability studies in thirty genotypes of pearl millet revealed high values of phenotypic and genotypic coefficients of variation and genetic advance for grain yield/plant. There was positive association of grain yield/plant with plant height, tillers/plant and ear weight, and negative association with days to ear emergence. Path analysis revealed direct contribution of tillers/ plant and ear weight 10 grain yield and indirect contribution to grain yield of ear length and girth through ear weight.